2015
DOI: 10.5798/diclemedj.0921.2015.01.0547
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrik disritmiler

Abstract: Pediatric dysrhythmias are rare but important causes of admission to pediatric clinics and emergency departments. Due to the development of successful surgical treatment of congenital heart diseases and improvements in the diagnostic tools, pediatric dysrhythmias are more frequently diagnosed. Although pediatric dysrhythmias are may be asymptomatic, they may manifest with weakness, dizziness, decrease in the effort capacity, easy fatigability, irregularity in heartbeats, palpitations, syncope and cardiac arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This is in line with research conducted in Bangladesh in 2018 where the results showed that the stunting factor was caused by parental education factors [12,13] . Other studies mention the factors that cause stunting are toddlers who have a history of infectious diseases, low birth weight infants (LBW), family income/economic factors [14,15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with research conducted in Bangladesh in 2018 where the results showed that the stunting factor was caused by parental education factors [12,13] . Other studies mention the factors that cause stunting are toddlers who have a history of infectious diseases, low birth weight infants (LBW), family income/economic factors [14,15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extremely important to determine the prognosis 3 . Generally, patients with SVT do not have concomitant congenital heart disease 5 . Although many studies have been conducted on SVT in infancy and childhood, these studies have been relatively limited in newborns without structural heart disease.…”
Section: Introductionmentioning
confidence: 99%